1990
DOI: 10.1364/ol.15.000792
|View full text |Cite
|
Sign up to set email alerts
|

Silicon antiresonant reflecting optical waveguides

Abstract: A new silicon waveguide called ARROW-C is proposed and analyzed at the 1.3-microm wavelength. The silicon structure uses two buried layers of SiO(2) or beta-SiC with a thickness of 14-23 nm to permit optical tunneling for leakymode propagation. A propagation loss of ~0.5 dB/cm is predicted for the TE(0) or the TM(0) mode in a 5-microm-thick Sicore layer. Novel silicon ARROW-A and ARROW-B guides are also discussed. The former uses a pair of buried GeSi layers; the latter employs buried SiO(2) and GeSi films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The defect density in this 5-layer sample is in the range of iO cm2, which is typical of the non-optimized or standard Simox process. This program was described in a paper by Soref and Ritter [12]. Based on other experiments [17,18], we firmly believe that the defect density in 6-layer 501 can be reduced below 1O cm2, either by multiple low-dose O1mplants [17] or by high-temperature implants [18].…”
Section: Construction Of Vertically Stacked Waveguidesmentioning
confidence: 86%
See 1 more Smart Citation
“…The defect density in this 5-layer sample is in the range of iO cm2, which is typical of the non-optimized or standard Simox process. This program was described in a paper by Soref and Ritter [12]. Based on other experiments [17,18], we firmly believe that the defect density in 6-layer 501 can be reduced below 1O cm2, either by multiple low-dose O1mplants [17] or by high-temperature implants [18].…”
Section: Construction Of Vertically Stacked Waveguidesmentioning
confidence: 86%
“…A number of silicon waveguides have been developed in the past four years, including: dopedlayer waveguides (n/nt p/p, n/p) [4], silicon-on-sapphire [5,6], GeSii on Si [7,8], Si I /Si [9], Si-on-Si02 [10, 1 1], and anti-resonant reflecting optical waveguides (ARROWs) which are 6-layer structures [12]. The modulation-doped guides have propagation losses of 5-15 dB/cm, but the other approaches listed are capable of lower losses.…”
Section: Silicon Waveguidesmentioning
confidence: 99%
“…Obviously, an optical device with such an enormous roughness would have unaffordable insertion losses if light was injected to the integrated optical device by end fire coupling. This is the main reason why after the cutting step, integrated optics devices need to be polished if one uses mechanical means of cutting, which is true for the case of conventional integrated optical devices based on silicon and other materials [13][14][15][16][17][18][19]. But in laser sawing of diamond, a majority of such post-polishing steps can be avoided and we have observed that the diamond crystals are sawn perfectly.…”
Section: Methodsmentioning
confidence: 99%
“…The original ARROW idea was further developed in [10][11][12] where new generations of ARROW structures with a high index core and a low index first cladding were proposed and characterised. These are the so-called ARROW-B (Fig.1, b) and ARROW-C configurations, which are applicable for SOI-based PCWs.…”
Section: Application Of the Arrow Concept In Photonic Crystal Waveguidesmentioning
confidence: 99%
“…A standard core thickness of classical ARROW structures is about 4-5 microns or more [10][11][12], and losses rapidly decrease with increasing core thickness. On the contrary, the thickness of the silicon core in an SOI-based PCW is severely limited by the requirement of a reasonable size of the photonic band gap.…”
Section: Application Of the Arrow Concept In Photonic Crystal Waveguidesmentioning
confidence: 99%